An introduction to d3.js : from scattered to scatterplot - Murray, Scott (College teacher) (O'Reilly Media, 2014)
"Confused by D3? Interested in coding data visualizations on the web, but don't know where to start? This video course will have you transforming data into visual images in no time at all, starting from scratch and building an interactive scatterplot by the end of the session. We'll use d3.js, the web's most powerful library for data visualization, to load data and translate values into SVG elements - drawing lines, points, and scaled axes to label our data."--Resource description page.